2001
DOI: 10.5194/nhess-1-127-2001
|View full text |Cite
|
Sign up to set email alerts
|

Study of electromagnetic emissions associated with seismic activity in Kamchatka region

Abstract: Abstract.A review of data processing of electromagnetic emission observation collected at the Complex Geophysical Observatory Karimshino (Kamchatka peninsula) during the first 5 months (July-November, 2000) of its operation is given. The main goal of this study addresses the detection of the phenomena associated with Kamchatka seismic activity. The following observations have been conducted at CGO: variations of ULF/ELF magnetic field, geoelectric potentials (telluric currents), and VLF signals from navigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This observatory began operation in 2011, being the first observatory of its kind in Spain. different components of the magnetic field [57], and the development of theoretical models for describing the intensity of the SR by disturbances in the ionosphere over the top of the epicenter of an earthquake. One of these theoretical models is based on ionosphere's vertical conductivity profile model, describing the regular Earth-ionosphere cavity.…”
Section: Elf Sensormentioning
confidence: 99%
“…This observatory began operation in 2011, being the first observatory of its kind in Spain. different components of the magnetic field [57], and the development of theoretical models for describing the intensity of the SR by disturbances in the ionosphere over the top of the epicenter of an earthquake. One of these theoretical models is based on ionosphere's vertical conductivity profile model, describing the regular Earth-ionosphere cavity.…”
Section: Elf Sensormentioning
confidence: 99%
“…Dologlou, 2008), the emission of electro-magnetic waves (e.g. Gladychev et al, 2001), the increase in Radon emission from the ground (e.g. Richon et al, 2003), geodetic variations (abnormal ground elevations, e.g.…”
Section: Earthquake Forecasting: Some Possible Precursorsmentioning
confidence: 99%
“…Therefore, Hayakawa et al developed the polarization method and found that the spectral power ratio of the vertical magnetic field (Z) to horizontal magnetic field (H) anomalously increased within the frequency range of 0.01 Hz prior to an earthquake on 8 August 1993 [12]. Polarization analysis has since been widely applied in seismic-electromagnetic studies [13][14][15][16][17][18][19]. In order to prevent the phenomenon that the amplitude of horizontal component (H) is small when the geomagnetic activity is weak but the polarization value increases abnormally, Ida and Li et al eliminated the geomagnetic data of the horizontal component with small amplitude during periods of weaker geomagnetic activity and developed an improved polarization method [5,20].…”
Section: Introductionmentioning
confidence: 99%